MODELING WIDTH ADJUSTMENT IN MEANDERING CHANNELS - Chen D.; Duan J.G. (My University, 2006)
Widening in sinuous channels occurs when the retreat of the outer bank exceeds the advance of the opposite bank. An analytical model is presented to simulate width adjustment in meandering channels of non-cohesive bank material resulting from bank erosion of two interactive processes: basal erosion and bank collapse. Bank collapse refers to the avalanche of non-cohesive material in the upper part of bank above water surface resulting from over-steepening of the bank surface due to basal erosion. The rate of basal erosion, including lateral erosion and bed degradation, is calculated as a function of the longitudinal gradient of sediment transport rate and strength of secondary flow. The transverse bed slope is treated as a variable that increases as channel sinuosity increases until the transverse bed slope reaches its maximum value. By simplifying the bank-collapse process for non-cohesive materials, the present study shows that the rate of bank-line retreat is determined by lateral erosion rate, near-bank bed-degradation rate, sediment grain size, and difference between flow depth and bank height. The time-dependent widening processes of two meandering channels in the laboratory are selected to test applicability of the model. The result shows that the simulated bank lines at individual time intervals closely match the experimental measurements. Whether the sinuosity of a meandering channel will increase or decrease is primarily determined by didtribution of the lngitudinal gradient of sediment transport rate along the channel. © 2005 Elsevier B.V. All rights reserved.
Keywords: ANALYTICAL MODEL; BANK EROSION; MEANDER; SEDIMENT TRANSPORT; WIDTH ADJUSTMENT